Réseau de surveillance de la croissance et production de l'huître creuse Crassostrea gigas dans le bassin de Marennes-Oléron : bilan de 12 années de suivi (1986-1998) - Le Moine, Olivier; Geairon, Philippe; Soletchnik, Patrick; Faury, Nicole; Goulletquer, Philippe; Robert, Stephane; Razet, Daniel; Heurtebise, Serge (2000)
Thiis report aims to study the oyster Crwsosrrea gigas growth and production over a 12 years time' s span in the bay of Marennes-DIeron. Results of 12 years of oyster growlh did not show any significant oyster biological productivity decrease, nor trend. ln contrast, annual growth showed a large variability, which will be correlated with environmental conditions. Moreover, annual growth variability was greater than the variability due to site location,. besides the Ronce experimental site. The later, located in the south west part of the bay of Marennes-Dleron, has been the leading oyster growth site since 1989. The annual shell growlh variabiliry was greater than oyster dry meat weight fluctuation . Both 1990 and 1991 years were characterized by the largest growth rates over the la st decade. Site ranking from one year to another was va riable with regard to shell weight and dry meat weight. The oyster growth observed during the fa ll was mostly correlated to a shell weight in crea se. During the last decade, only 25% of experimental sites were characterized by a fa ll and, although limited, oyster meat growth. A significant 4-6% Iipids concentration decrease was correlated with the summer spawning event. The carbohydrates concentration did not show any significant trend over the early monitoring development. High prote in concentrations as weil as the proteins-carbohydrates-Iipids sum of concentrations are correlated with high oyster growth rates. Ce rapport présente le résultat de 12 années d'étude sur la croissance de l'huître creuse dans le Bassin de Marennes Oléron. En 12 ans, il n'apparaît pas de tendance à la baisse des performances de croissance, mais bien des fluctuations inter annuelles qui seront à corréler avec les conditions environnementales des élevages. Les variations inter annuelles de croissance au cours des 12 années d'étude sont de plus grande amplitude que celles résultant de la localisation des sites expérimentaux (exception faite de la station de Ronce). Le site de Ronce, dans la partie ...